Descriptive Study of the Relationship between Complaining and Faith in Facing Suffering Based on Job Chapter 3 - Pardomuan Marbun; Charisma Melniatri (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
This article discusses a descriptive study of the relationship between complaints and faith and belief in dealing with suffering based on job. The research method used is library research to find data related to complaints and also faith, specifically data regarding the story of Job's complaints in the third chapter of the book of Job. From the research conducted, it is found that the complaints expressed by Job show Job's understanding of his humanity, which means that Job is an ordinary human being who is the same as humans in general. Therefore, as an ordinary human being, complaining about the regret of the day of birth, expecting death at birth and despairing to the point of wanting death are complaints that are closely related to the lack of faith. In this case, when a believer experiences suffering that is so severe that it suppresses his mind, emotions and even his physical health, it can erode his faith in God. Keywords: Job, Old Testament Theology, Faith, Complaint, Suffering